‘Tied Visas’ and Inadequate Labour Protections: A formula for abuse and exploitation of migrant domestic workers in the United Kingdom - Demetriou, Daphne (Anti-Trafficking Review, 2015)
This article examines the link between restrictive immigration schemes, specifically ‘tied visas’ and the selective application of labour laws, with exploitation of workers. It focuses on the situation of migrant domestic workers, who accompany their employers to the United Kingdom (UK) and are exposed to both an excessively restrictive visa regime, introduced in April 2012, and limited labour protections. The immigration status of these workers is currently tied to a named employer, a restriction that traps workers into exploitative conditions, often amounting to forced labour, servitude or slavery. Additionally, current UK labour laws are either not enforced or not applicable to domestic workers. The article concludes that unless the current immigration regime is abolished and comprehensive labour law protections are extended to migrant domestic workers, exploitation will continue.